Penerapan Pohon Keputusan untuk Memetakan Gaya Kognitif Berdasarkan Kesalahan Siswa dalam Berpikir Aljabar Menurut Teori Newman - Mumtaza, Mutiara; Rizki, Nanda Arista (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
An understanding of Field Independent (FI) and Field Dependent (FD) cognitive styles is important for teachers because these two styles affect the way students understand and process information, which ultimately has an impact on the effectiveness of learning. This study aimed to build a decision tree model to map the cognitive style of students based on errors that students make in solving algebra problems according to Newman's error theory. The method used in this study was a quantitative approach with the ID3 algorithm in decision tree modeling. The instruments used include the GEFT test to identify students' cognitive style and the basic algebra ability test containing 6 aspects of algebra ability according to Lew, i.e. generalization, abstraction, analytical thinking, dynamic thinking, modeling, and organization. The decision tree model was built based on the errors made by students according to Newman's error theory. The results showed that the decision tree generated from algebra problems in the generalization aspect had an accuracy of 82.5%. This decision tree has a main attribute in the form of process skill errors, which can map the cognitive style of students as FI or FD. This decision tree formed three implication rules, which became the basis for classifying the cognitive style of students. This finding was expected to be a guide for teachers in designing a more adaptive and efficient learning strategy with an approach that is on the cognitive style of students to improve students' algebraic thinking ability. Keywords: Cognitive Style, Algebraic Thinking Ability, Decision Tree, Newman's Error Theory